The Association Between the Triglyceride-to-High-Density Lipoprotein Cholesterol Ratio and the Risk of Progression to Diabetes From Prediabetes: A 5-year Cohort Study in Chinese Adults - Sun, Yanfei; Wang, Zhibin; Huang, Zhiqiang; Hu, Haofei; Han, Yong (Frontiers in Endocrinology, 2022)
Objective: Evidence regarding the relationship between the triglyceride-to-high-density lipoprotein cholesterol (TG/HDL-c) ratio and the risk of progression from prediabetes to diabetes remains limited. The purpose of our study was to investigate the relationship between the TG/HDL-C ratio and incident diabetes in prediabetic patients. Methods: This retrospective cohort study covered 32 regions and 11 cities in China and consecutively and non-selectively collected data from 15017 patients with diabetes who had received a health check from 2010 to 2016. Data was obtain from the DATADRYAD database (www.datadryad.org). Cox proportional-hazards regression model with cubic spline functions and smooth curve fitting (cubic spline smoothing) was used to explore the nonlinear relationship between the baseline TG/HDL-c ratio and the risk of diabetes in patients with prediabetes. In addition, we performed a series of sensitivity and subgroup analyses. Results: The mean age of the included individuals was 50.95±13.48 years old, and 9745 (64.51%) were male. The median (interquartile range) TG/HDL-c ratio was 1.09 (0.69-1.72). During a median follow-up time of 3.05 years, 1731 (11.46%) patients had a final diagnosis of diabetes. The analysis after adjusting for covariates, showed that TG/HDL-c ratio was positively related to incident diabetes in patients with prediabetes (HR=1.111, 95%CI 1.061-1.164). Participants with the highest TG/HDL-c ratio(Q4) had higher diabetes incidence rates than those with the lowest TG/HDL-c ratio(Q1) (p<0.001 for the trend). There was a nonlinear relationship between the TG/HDL-c ratio and the risk of diabetes, and the inflection point of the TG/HDL-c ratio was 1.415. The effect sizes (HR) on the left and right sides of the inflection point were 1.336 (95%CI:1.134-1.573) and 1.055 (95%CI:0.988-1.126), respectively. The sensitivity analysis demonstrated the robustness of these results. Conclusion: This study demonstrates a positive, nonlinear relationship between the TG/HDL-c ratio and the risk of diabetes in Chinese patients with prediabetes. Aggressive intervention from a treatment perspective is required to lower the TG/HDL-c ratio below the inflection point (1.415) by lowering TG or increasing HDL-c levels.